Altered Mental Status and a Not-So-Benign Rash. (19th October 2011) - Bodhit, Aakash N.; Stead, Latha Ganti
Abstract : Introduction . The authors are presenting a case of Thrombotic Thrombocytopenic Purpura (TTP) that presented with complaints of altered mental status and found to have petechiae. Case Presentation . An 81-year-old female patient presented to the Emergency Department (ED) of a tertiary care hospital with chief complains of dizziness, slurred speech, and weakness. She was found to have lower extremity petechiae on physical examination. On blood exam, she had thrombocytopenia, and her peripheral blood smear showed schistocytes. Her renal function was also impaired. The CT scan of head was without any abnormality. She was finally diagnosed as having TTP and transferred to ICU but ultimately passed away. Conclusion . TTP is a rare syndrome with preventable mortality if diagnosed early and managed appropriately with plasmapheresis. The Emergency Department physicians should be aware of the presenting symptoms and signs of TTP.